Does a Standalone Cancer Center Improve Head and Neck Microsurgical Outcomes? - Tamplen, Matthew L.; Tamplen, Jesse; Torrecillas, Vanessa; Seth, Rahul; Ricceri, Santo; Hemmat, Shirin; Heaton, Chase; Ryan, William R.; Knott, P. Daniel (Journal of Reconstructive Microsurgery, 2017)
Objectives To evaluate the role of hospital setting (standalone cancer center vs. large multidisciplinary hospital) on free tissue transfer (FTT) outcomes for head and neck reconstruction.Methods Medical records were reviewed of 180 consecutive patients undergoing FTT for head and neck reconstruction. Operations occurred at either a standalone academic cancer center (n = 101) or a large multidisciplinary academic medical center (n = 79) by the same surgeons. Patient outcomes, operative comparisons, and hospital costs were compared between the hospital settings.Results The cancer center group had higher mean age (65.2 vs. 60 years; p = 0.009) and a shorter mean operative time (12.3 vs. 13.2 hours; p = 0.034). Postoperatively, the cancer center group had a significantly shorter average ICU stay (3.45 vs. 4.41 days; p < 0.001). There were no significant differences in medical or surgical complications between the groups. Having surgery at the cancer center was the only significant independent predictor of a reduced ICU stay on multivariate analysis (Coef 0.73; p < 0.020). Subgroup analysis, including only patients with cancer of the aerodigestive tract, demonstrated further reduction in ICU stay for the cancer center group (3.85 vs. 5.1 days; p < 0.001). A cost analysis demonstrated that the reduction in ICU saved $223,816 for the cancer center group.Conclusion Standalone subspecialty cancer centers are safe and appropriate settings for FTT. We found both reduced operative time and ICU length of stay, both of which contributed to lower overall costs. These findings challenge the concept that FTT requires a large multidisciplinary hospital.Level of Evidence 4.
Keywords: head and neck reconstructive surgery; microvascular surgery; outcomes; cost-effectiveness